Strategies of consecutive interpretation in joint press conferences - Bekova, Zh.K.; Islam, A.; Bauyrzhan, G. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
This article deals with problems of interpretation of political discourse in joint press conference. Novelty of research is identified by the lack of domestic publications in the field of Translation studies on press conferences in the context of Kazakhstan’s foreign policy. Article examines characteristic features of consecutive interpretation of political media discourse. The need of effective strategies that help to provide adequate interpretation is identified and justified. On the basis of the study the authors suggest that background knowledge on communicative situation enables interpreter to solve tasks caused by time deficiency and different semantic structures. It is proved that use of compression, decompression and re-ordering string in consecutive interpretation is key to reach communicative equivalence in target text. Results show that juxtaposition of strategies in one discursive segment illustrates that inherent cognitive feature of interpretation process. Article consists of literature review, methods of research, description and analyses of research material.
Бірлескен баспасөз конференциясын ізбе-із аудару барысында қолданылатын стратегиялар
Стратегии последовательного перевода на совместных пресс-конференциях
Keywords: political communication; joint press conference; consecutive interpretation; strategies; compression; decompression; re-ordering string; source text (ST); target text (TT)